On Character of Morality - Krakauskas, Edmundas (Problemos, 1985)
Morality reveals itself first in customs regulating intercourse of people. More abstract concepts of good, evil and the like provide rather general understanding of morality. Customs characterize a current morality. Readiness of the studies in ethics is guaranteed by deeper investigations of the ‘active’ morality, i.e., customs. The investigation of the customs of socialist society is of prime importance for the Marxist ethics.